Comparing skipjack tuna catch and oceanographic conditions at FAD locations in the Gulf of Bone and Makassar Strait. (November 2019) - Hidayat, R; Zainuddin, M; Mallawa, A; Mustapha, M A; Putri, A R S
Abstract: This study aimed to compare the differences between characteristics of skipjack tuna ( Katsuwonus pelamis ) fishing grounds in the Gulf of Bone and in the Makassar Strait. We used catch size and volume data from FAD areas in the Gulf of Bone and Makassar Strait, and satellite image data including sea surface temperature (SST) and chlorophyll-a (CHL-a). We used ECDF (Empirical Cumulative Distribution Function) analysis to determine the relationship between the oceanographic variables and skipjack CPUEs that occurred in the Gulf of Bone and the Makassar Strait. The resulting data for the two fishing areas were then compared using the Spatial Analyst in ArcGIS 10.2. The analysis showed that the average SST and CHL in the Gulf of Bone (30°C and 0.3 mg m −3 ) were higher than those in the Makassar Strait (29.5°C and 0.24 mg m −3 ). The size of skipjack tuna caught in the two fishing areas was different. The mean total length of Skipjack tuna caught in the Makassar Strait was 23 cm, while in the Gulf of Bone it was 41 cm. There was little overlap in the size distributions. These data suggest that skipjack tuna caught around FADs in the Gulf of Bone tend to be larger than those in the Makassar Strait which may be stimulated by relatively higher productivity and thus feeding opportunity.